Thermal and economical optimization for a finned-tube, air-cooled condenser design of a roof-top bus air-conditioning system - Khamis Mansour, M.; Musa, M. N.; Wan Hassan, M. N. (Professional Engineering Publishing, 2007)
The current paper presents a methodology of a design optimization technique that can be useful in assessing the best configuration of a finned-tube condenser, using a thermal and economical optimization approach. The assessment has been carried out on an air-cooled finned-tube condenser of a vapour compression cycle for a roof-top bus air-conditioning system at a specified cooling capacity. The methodology has been conducted by studying the effect of some operational and geometrical design parameters for the condenser on the entire cycle exergy destruction or irreversibility, air-conditioning system coefficient of performance (COP), and total annual cost. The heat exchangers for the bus air-conditioning system are featured by a very compact frontal area due to the stringent space limitations and structure standard for the system installation. Therefore, the current study also takes in its account the effect of the varying design parameters on the condenser frontal area. The irreversibility due to heat transfer across the stream-to-stream temperature-difference and due to frictional pressure-drops is calculated as a function of the design parameters. A cost function is introduced, defined as the sum of two contributions, the investment expense of the condenser material and the system compressor, and the operational expense of air-conditioning system, which is usually driven by an auxiliary engine or coupled with the main bus engine. The optimal trade-off between investment and operating cost is therefore investigated. A numerical example is discussed, in which, a comparison between the commercial condenser design and optimal design configuration has been presented in terms of the system COP and condenser material cost. The results show that a significant improvement can be obtained for the optimal condenser design compared to that of the commercial finned-tube condenser, which is designed based on the conventional values of the design parameters.